2015
DOI: 10.3960/jslrt.55.169
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral T-Cell Lymphoma, Not Otherwise Specified and Concurrent Seminoma in Testis

Abstract: Concurrent seminoma and malignant lymphoma of the testis is rare. We present a case of concurrent seminoma and peripheral T-cell lymphoma, not otherwise specified (PTCL-NOS) in a 54-year-old man who complained of painless left testicular enlargement. Radical left orchiectomy was performed. Macroscopically, the tumor (4.0 × 3.0 cm) was creamy, soft, and homogeneous, and microscopic evaluation revealed an alveolar structure of large cells that formed sheets, as well as colonization by other abnormal cells in a 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Our literature review found a few rare examples of patients with synchronous seminoma and lymphoid neoplasms. All of these patients—including the present one—were aged more than 50 years [ 3 6 ]. Singh et al [ 3 ] reported a case of synchronous classical Hodgkin lymphoma in the mediastinal/intraabdominal lymph nodes and right testicular seminoma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our literature review found a few rare examples of patients with synchronous seminoma and lymphoid neoplasms. All of these patients—including the present one—were aged more than 50 years [ 3 6 ]. Singh et al [ 3 ] reported a case of synchronous classical Hodgkin lymphoma in the mediastinal/intraabdominal lymph nodes and right testicular seminoma.…”
Section: Discussionmentioning
confidence: 99%
“…Jacobsen et al [ 5 ] described a case of metastatic seminoma and concurrent follicular lymphoma, grade 1 in a supraclavicular lymph node. Only one case of concurrent seminoma and PTCL, NOS in the same testis has been reported [ 6 ]. Because of indolent clinical courses of CLL and seminoma, additional/adjuvant therapy was not administered for both tumors in the present case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation